Enhancing motor learning through Dyad practice: Contributions of observation and dialogue - Granados, C.; Wulf, G. (Research Quarterly for Exercise and Sport, 2007)
It has been shown that practice in dyads, as compared to individual practice, can enhance motor learning and increase the efficiency of practice (as two participants can be trained at the same time; Shea, Wulf, & Whitacre, 1999). The dyad practice protocol used by Shea et al. included both observation and dialogue between partners. Thus, it was not clear whether the learning benefits of dyad practice were due to observation, dialogue, or both. The present study examined the individual and interactive effects of observation and dialogue. The task used was speed cup stacking. Participants practiced under one of four conditions: observation/dialogue, observation/no dialogue, no observation/dialogue, and no observation/no dialogue. The two conditions that included observational practice were more effective (i.e., produced faster movement times) than the two conditions without it, both during practice and on a retention test performed under individual performance conditions. This suggests that the learning advantages of dyad practice are primarily due to the opportunity to observe another learner.